2016
DOI: 10.1136/oemed-2016-103613
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in EYA4 on the risk of noise-induced hearing loss in Chinese steelworks firm sample

Abstract: The research suggests that EYA4 genetic variant and its interaction with noise levels may modify the susceptibility to develop noise-induced hearing loss in Chinese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…While occupational noise exposure is regulated, a person’s lifetime noise exposure is extremely difficult to quantify. The effects of noise exposure may be combined with other effects from smoking, impaired vascular flow, and genetic predisposition (Yang et al 2016). These factors make identifying noise exposure as the sole contributor to a person’s hearing loss impossible.…”
Section: Discussionmentioning
confidence: 99%
“…While occupational noise exposure is regulated, a person’s lifetime noise exposure is extremely difficult to quantify. The effects of noise exposure may be combined with other effects from smoking, impaired vascular flow, and genetic predisposition (Yang et al 2016). These factors make identifying noise exposure as the sole contributor to a person’s hearing loss impossible.…”
Section: Discussionmentioning
confidence: 99%
“…Dobie and Humes (2017) have suggested that humans are less susceptible to TTS and argue that they are therefore less likely to sustain noise-induced cochlear synaptopathy than rodents. There is also evidence that certain individuals may be more or less genetically susceptible to damage from noise exposure/s than others (Abreu-Silva et al, 2011;Kowalski et al, 2014;Yang et al, 2016;Zhang et al, 2014). Furthermore, there may be interactive effects between genetic susceptibility and environmental factors, such as exposure to ototoxic agents.…”
Section: Differences Between Animal and Human Researchmentioning
confidence: 99%
“…Current studies have shown that the polymorphisms of potassium ion channel genes (like KCNQ4 and KCNE1 ) [ 14 , 15 ], catalase ( CAT ), protocadherin 15 ( PCDH15 ), myosin 14 ( MYH14 ) [ 16 ] and heart shock protein ( HSP70 ) [ 17 ] detected in different populations are significantly related to the development of NIHL. In addition, studies conducted by our research group has also found that heart shock protein ( HSP70 ) [ 18 ], eye absent homolog 4 ( EYA4 ) [ 19 ], suggestive POU-domain transcription POU4F3 and Grainyhead-like2 ( GRHL2 ) [ 20 ] may be associated with the susceptibility to NIHL.…”
Section: Introductionmentioning
confidence: 99%